Arnotts goes global managing change in large organisations - Loftus-Hills, Jeremy; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 1995)
This program looks at Arnotts response to pressures to'go global' and its attempts to become a world class manufacturer by bridging the gap between mass production and lean manufacture. It investigates the resulting changes in management policies and documents the creation of self-management teams, which have resulted in improvements to the efficiency and effectiveness of the Arnotts production process
Title from title screen
Executive producer, Neil Barrett ; editor, Stephen Maggs
Narrator: Justin Shorty
DVD format
Keywords: Arnotts Ltd; Corporate culture -- Australia; Organizational change -- Australia